2021
DOI: 10.1002/hed.26738
|View full text |Cite
|
Sign up to set email alerts
|

The preoperative C‐reactive protein–lymphocyte ratio and the prognosis of oral cavity squamous cell carcinoma

Abstract: Background We aimed to investigate the preoperative C‐reactive protein (CRP)–lymphocyte ratio (CLR) as a prognostic biomarker in oral cavity squamous cell carcinoma (OSCC). Methods Three hundred and sixteen patients with OSCC treated with curative surgery were retrospectively assessed and the receiver operating characteristic curve was used to evaluate the discriminative ability of inflammatory markers. The prognostic value of CLR was investigated with Cox proportional hazards analysis. Results The CLR cutoff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The prognostic role of CLR has been studied in other malignancies, too. According to a study which observed CLR in oral malignancy, elevated level of CLR was associated with better prognostic performance compared to other inflammatory markers in subjects with squamous cell carcinoma 11 . Similarly, Meng et al investigated CLR in patients with colorectal cancer and reported that patients with high CLR had shorter overall survival than those with low CLR levels 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic role of CLR has been studied in other malignancies, too. According to a study which observed CLR in oral malignancy, elevated level of CLR was associated with better prognostic performance compared to other inflammatory markers in subjects with squamous cell carcinoma 11 . Similarly, Meng et al investigated CLR in patients with colorectal cancer and reported that patients with high CLR had shorter overall survival than those with low CLR levels 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The widely used AJCC staging system considers only tumor characteristics. However, patient factors such as antitumor immunity, systemic inflammation, and nutritional status are also significantly associated with the survival outcomes of OSCC 12 , 13 , 19 , and not considering these factors when prognosticating may impair the accuracy of survival predictions. Given that CALLY index integrates the peripheral lymphocyte count with serum CRP and albumin levels in an easily calculable manner, we developed a prognostic nomogram incorporating the CALLY index, AJCC stage system, and clinicopathological features to provide individualized 3-year and 5-year OS estimations and favorable results were obtained (C-index: 0.797; AUC: 0.81).…”
Section: Discussionmentioning
confidence: 99%
“…The value of using clinicopathological features as prognostic factors was carefully reviewed; these features were as follows: sex; age at diagnosis; underlying comorbidities according to the Charlson comorbidity index (CCI) 18 ; tumor subsite and size; pathological cancer stage, as defined by the American Joint Committee on Cancer eighth-edition cancer staging manual; ENE and PNI status; cancer cell differentiation; depth of invasion (DOI); nearest surgical margin; the need for and types of adjuvant therapy; and personal health-related habits. Cigarette smoking was defined as smoking ≥1 packet of cigarettes daily for ≥1 year; alcohol drinking was defined as consuming ≥2 alcoholic beverages weekly for more than half a year; and betel nut consumption was defined as chewing ≥3 betel nuts daily for ≥1 year 19 . Each patient was classified as having no, one, and two or all exposures if they had none, one, and two or more of the aforementioned personal habits, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Two Taiwanese studies observed that a squamous cell carcinoma antigen level of 2.0 ng/ml and a CRP level of 5.0 mg/L were associated with the prognosis of OSCC ( 32 ) and pharyngolaryngeal carcinoma ( 33 ). Ko et al reported that the preoperative CRP–lymphocyte ratio was related to the prognosis of patients with OSCC ( 34 ). The CRP/albumin ratio could predict poor survival in patients with hypopharyngeal and laryngeal cancer ( 35 ).…”
Section: Discussionmentioning
confidence: 99%